Assessment of threat of concurrent SARS-CoV-2 and DENV infection in the COVID-19 pandemic in Brazil in 2020: diagnostic and immunological findings - Rodrigues, Joyce Carnevale; Familiar-Macedo, Débora; Medeiros, Thalia; Carvalho, Fabiana Rabe; Almeida, Jorge Reis; Silva, Andrea Alice; dos Santos, Flávia Barreto; de Souza, Luiz José; Damasco, Paulo Vieira; Azeredo, Elzinandes Leal; de-Oliveira-Pinto, Luzia Maria (Frontiers in Tropical Diseases, 2023)
The first peak of COVID-19 in Brazil was between April and May 2020, at a time of the year when outbreaks of other tropical diseases, such as dengue, would be expected. COVID-19 and dengue have similar pathogenesis. In general, both may lead to mild symptoms but may also cause severe and even fatal symptoms, especially in patients with comorbidities and probably in cases of overlapping infections. The general objective of this study was to assess whether, during the 2020 pandemic, there were cases of concomitant infection between SARS-CoV-2 and DENV. For this, we sought to address three specific objectives: (i) to evaluate the specificity and sensitivity of commercial serological anti-SARS-CoV-2 kits using plasma samples from patients with dengue and healthy donors recruited before COVID-19; in the case of confirmed cases of COVID-19/dengue, (ii) to evaluate the clinical evolution of these coinfected patients, compared with mono-infected patients; and, considering the involvement of CCL2 and CXCL8 chemokines in fatal acute lung injury, (iii) to quantify chemokines in COVID-19 patients in order to correlate them with COVID-19/dengue severity and cases. Our results showed that commercial IgA and IgG anti-SARS-CoV-2 kits presented high sensitivity and specificity. Among the 57 COVID-19 patients, anti-DENV IgM was detected in five (8.8%). COVID-19/dengue coinfected patients showed no clinical worsening of COVID-19. Lastly, CCL2 and CXCL8 appeared to be good markers of COVID-19 severity and did not show increased levels in the cases of coinfection.